2001
DOI: 10.1046/j.1469-7580.2001.19960725.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of mucosa and serosa in the obstructed intestine of rats

Abstract: After a surgically induced partial obstruction of the small intestine (ileum) in adult rats there is an accumulation of ingesta and a progressive enlargement of the lumen accompanied by wall thickening : over a period of 2-3 wk the circumference of the hypertrophic intestine increases by a factor of 2n7 and the thickness of the musculature increases more than threefold, while the length of the ileum (measured at the mesenteric attachment) remains unchanged. The villi become markedly larger and more elo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
2
29
0
Order By: Relevance
“…The gastrointestinal partial obstruction model has been used in a number of experimental studies, primarily on changes in morphology and motility patterns [8,17,26]. It was demonstrated that pronounced morphologic and histologic changes were induced by the partial banding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gastrointestinal partial obstruction model has been used in a number of experimental studies, primarily on changes in morphology and motility patterns [8,17,26]. It was demonstrated that pronounced morphologic and histologic changes were induced by the partial banding.…”
Section: Discussionmentioning
confidence: 99%
“…However, similar detailed data are not available for the partially obstructed intestine despite the initial work by Gabella [16], SchulzeDelrieu et al [17] and Storkholm et al [5,6,14]. Because of morphologic remodeling in the small intestine during obstruction [8,10], the biomechanical properties are also bound to change. Because biomechanics deals with the relation between stress (force per area) and strain (deformation), we consider the stress-strain relationship of the intestinal wall (stiffness) as the relevant quantitative remodeling parameters because they are measures of the nonuniformity of growth or resorption in different parts of the intestinal wall [13,18].…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…The phenomena of SMC hypertrophy and hyperplasia, which occurs during partial bowel obstruction, has been previously well described. 13,22,23 Inflammation may also cause SMC hypertrophy within the GI tract. 24,25 However, the molecular mechanism remains less understood.…”
Section: Discussionmentioning
confidence: 99%
“…Muscle hypertrophy and hyperplasia of mural ganglia were observed in the deer proximal to the tumor mass, features thought to be induced by the increased workload required to overcome the obstruction. 4,5 Spontaneous intestinal neoplasia in animals is considered a rare event, 23 strongly suggesting that particular predisposing risk factors must be at play to account for such a high incidence of neoplasia in the study herd. This may reflect a genetic predisposition and/or environmental exposure to carcinogens.…”
Section: Discussionmentioning
confidence: 99%